2012
DOI: 10.1021/jp304429f
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond Pulse Radiolysis Study of Highly Concentrated Nitric Acid Solutions: Formation Mechanism of NO3 Radical

Abstract: The formation of nitrate radical, NO(3)(•), is observed for the first time directly by picosecond pulse radiolysis of highly concentrated nitric acid solutions. The experimental yield of NO(3)(-) ionization is deduced from the pulse-probe transient absorption measurements in the visible region where this radical absorbs. On the basis of the value of the extinction coefficient of nitrate radical at 640 nm equal to 1300 M cm(-1), the experimental yield of NO(3)(•) at 20 ps is found to be around 0.36 × 10(-7), 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 32 publications
(62 reference statements)
4
33
0
Order By: Relevance
“…Both protonating the dianion NO 3 2− (reaction (9)) (Shkrob et al, 2011;Balcerzyk et al, 2012;Katsumura et al, 1991) and dissociative O 2 À transfer (reaction (10)) (Cook et al, 2001) have been proposed to explain the conversion of NO 3 2− to NO 2 . The resulting NO 2 radical reacts with DCH18C6 via H-atom abstraction from polyether ring to generate the macrocyclic -CH 2 -CḢ-O-radicals (reaction (11) …”
Section: Post-irradiation Thermal Reactionsmentioning
confidence: 99%
“…Both protonating the dianion NO 3 2− (reaction (9)) (Shkrob et al, 2011;Balcerzyk et al, 2012;Katsumura et al, 1991) and dissociative O 2 À transfer (reaction (10)) (Cook et al, 2001) have been proposed to explain the conversion of NO 3 2− to NO 2 . The resulting NO 2 radical reacts with DCH18C6 via H-atom abstraction from polyether ring to generate the macrocyclic -CH 2 -CḢ-O-radicals (reaction (11) …”
Section: Post-irradiation Thermal Reactionsmentioning
confidence: 99%
“…The fuel dissolution is in aqueous nitric acid and is radioactive due to fission product and actinide decay. The • NO 3 radical is produced during the high‐energy irradiation of HNO 3 , and this radical may also act as an oxidizing agent for the organic ligands resulting in deleterious effects on solvent extraction performance in this condensed phase system.…”
Section: Introductionmentioning
confidence: 99%
“…), we found that the k Se2+X -k e+X and k SOH2+X -k OH+X rela tions can be expressed by: (18) A possible cause of the significant deviation of the values of k Se2+X for some systems ( Cu ++ ) shown in Table. [24] has to be considered. Since the processes of the formation and decay of NO 3 are not fully understood [25], it may be assumed that NO 3 can interfere in the H 2 formation process, scavenging electrons in the spurs:…”
Section: Simulation Of the H 2 O 2 Yieldmentioning
confidence: 99%